Effect of Feeding Bacillus subtilis Spores to Broilers Challenged with Salmonella enterica serovar Heidelberg Brazilian Strain UFPR1 on Performance, Immune Response, and Gut Health - Hayashi, Ricardo Mitsuo; Lourenço, Mariana Camargo; Kraieski, Antônio Leonardo; Araujo, Raquel Bighetti; Gonzalez-Esquerra, Ricardo; Leonardecz, Eduardo; da Cunha, Anderson Ferreira; Carazzolle, Marcelo Falsarella; Monzani, Paulo Sérgio; Santin, Elizabeth (Frontiers in Veterinary Science, 2018)
Salmonellosis is a poultry industry and public health concern worldwide. Recently, Salmonella enterica serovar Heidelberg (SH) has been reported in broilers in Brazil. The effect of feeding a blend of three strains of Bacillus subtilis (PRO) was studied in broilers orally challenged (107 CFU/chick) or not with a SH isolated in south of Brazil (UFPR1 strain). Twelve male Cobb 500 broilers per pen were randomly assigned to 6 treatments in a 3x2 factorial experiment where PRO was added at 0, 250 or 500g/ton of broiler feed and fed to either SH-challenged (SH Control, SH+PRO 250 and SH+PRO 500) or non-challenged birds (Control, PRO 250 and PRO 500). Broiler performance, histologic alterations in intestinal morphology, Salmonella quantification and immune cells counts in liver (macrophages, T CD4+ and T CD8+) were analyzed. Changes in the intestinal microbiota of broilers were also studied by metagenomics for Control, SH Control, SH+PRO 250 and SH+PRO 500 only. Feeding PRO at 250 or 500g/ton reduced SH counts and incidence in liver and cecum at 21 days of age. It was observed that PRO groups increased the macrophage mobilization to the liver in SH-challenged birds (P<0.05) but reduced these cells in the liver of non-challenged birds, showing an interesting immune cell dynamics effect. PRO at 250g/ton did not affect gut histology, but improved animal performance (P<0.05) while PRO at 500/ton did not affect animal performance but increased histologic alteration related to activation of the defense response in the ileum in SH challenged birds compared to control birds (P<0.05). SH+PRO 500 group presented a more diverse cecal microbiota (Shannon-Wiener index; P<0.05) compared to Control and SH Control groups; while SH+PRO 250 had greater ileal richness (JackkNife index) compared to Control (P<0.05). PRO was effective in reducing Salmonella colonization in liver and cecum when fed at 250 or 500g/ton to broilers inoculated with SH strain UFPR1. PRO promotes positive alterations in performance (at 250g/ton), immune modulatory effect in the gastrointestinal tract, SH reduction and intestinal microbiota modulation.